SERS discrimination of single DNA bases in single oligonucleotides by electro-plasmonic trapping - Jian-An Huang (Nature Portfolio, 2019)
Sensing DNA bases by surface-enhanced Raman spectroscopy (SERS) in plasmonic nanopores has suffered from rapid flow through of molecules. Here, the authors attach DNA molecules to gold nanoparticles which, due to electro-plasmonic trapping, allow for controlled residence times and discrimination of single nucleotides.